Herbivoria por Atta sexdens rubropilosa Forel, 1908 sobre espécies arbóreas em restauração florestal - Ferreira, Beatriz Zidioti [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Leaf-cutting ants are herbivores that have great potential to shape communities and ecosystems functioning and are therefore considered ecosystem engineers. Most damage caused by leaf-cutting ants occurs in young leaves, thus influencing seedlings establishment and development, possibly delaying the restoration processes. The aim of this study was to verify if leaf-cutting ants can act as a biotic filter determining species composition of communities undergoing restoration, and if they can lead to extinction some species or compromise the structure of restored forests. The study was conducted in a riparian forest undergoing restoration since 1990, at the municipality of Tarumã-SP. We simulated the arrival of forest species to the site being restored, by introducing 20 seedlings of tree species of the regional flora, representing different functional guilds. We planted 20 individuals of each species in a large gap, with about 500 m², surrounded by the existing forest. Planting density was defined based on the density in which plants the same size of the seedlings planted occur in the native forest in the study region. The development of each individual and herbivory by ants were recorded from December 2012 to December 2013. We compared the frequency of herbivory among species and investigated possible patterns of resistance to herbivory associated with functional attributes of the tree species. We also evaluated the effect of selective herbivory on the diversity of the community in restoration through time. From the management perspective, we investigated whether or not the frequency of herbivory by ants is associated with time after planting (acclimation), and if mortality rates depend on the size of the seedlings planted. The frequency of herbivory was different among the tree species planted, resulting in different rhythms and different mortality rates among species. As a consequence, ...

Formigas cortadeiras são herbívoros que possuem grande potencial para modificar comunidades e ecossistemas em sucessão e por isso são considerados engenheiros do ecossistema. A maioria dos danos causados por formigas ocorre em folhas jovens, o que dificulta o estabelecimento e o desenvolvimento inicial das mudas plantadas, de modo que podem atrasar a recuperação da estrutura e da diversidade, no caso de plantios de restauração. O objetivo do presente estudo foi verificar se formigas cortadeiras podem atuar como filtro biótico a determinar a composição de espécies das comunidades vegetais, se podem levar à extinção algumas espécies ou se podem comprometer a estrutura das florestas restauradas. Para isto, instalamos experimento em plantio de restauração de floresta ripária realizado em 1990, no município de Tarumã, SP. O experimento baseou-se na simulação da entrada de espécies na floresta restaurada, por meio da introdução de mudas de 20 espécies arbóreas nativas da flora regional, representativas de diferentes guildas funcionais. Plantamos 20 indivíduos de cada espécie em uma clareira grande, com cerca de 500 m², circundada pela floresta já existente. A densidade de plantio foi definida com base na densidade em que plantas do porte das mudas ocorrem em florestas naturais da região. O desenvolvimento de cada muda plantada e os ataques por formigas foram registrados de dezembro de 2012 a dezembro de 2013. Foi analisada comparativamente a frequência de ataques de herbivoria por formigas entre as espécies arbóreas e investigamos possíveis padrões de resistência à herbivoria associados a atributos funcionais dessas espécies. Avaliamos também o efeito da herbivoria seletiva sobre a diversidade da comunidade em restauração. Do ponto de vista de manejo, investigamos se a frequência de ataques de herbivoria por formigas está associada à aclimatação e se a mortalida ...
Selective herbivory by atta sexdens rubropilosa forel, 1908 on tree species in forest restoration
Keywords: Formiga-cortadeira; Ecologia florestal; Recuperação ecológica; Ecossistemas - Restauração; Ants